2020
DOI: 10.1086/710388
|View full text |Cite
|
Sign up to set email alerts
|

Niche Breadth: Causes and Consequences for Ecology, Evolution, and Conservation

Abstract: Niche breadth is a unifying concept spanning diverse aspects of ecology, evolution, and conservation biology. Niche breadth usually refers to the diversity of resources used or environments tolerated by an individual, population, species, or clade. Here we review key research in ecology, evolution, and conservation biology in light of niche breadth. Namely, we explore the role of niche breadth in shaping geographic distributions and species richness from local to landscape scales, how niche breadth evolves and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(153 citation statements)
references
References 231 publications
4
128
1
Order By: Relevance
“…Evidence from these studies seems to suggest that lower-and upper-climatic niche limits might be uncoupled over evolutionary time, such that patterns of climatic niche breadth might be driven more by changes in one of the climatic niche boundaries, particularly in the case of temperature. However, despite this indirect evidence, few studies have directly assessed variation in evolutionary rates between different climatic range limits (Carscadden et al, 2020). In the largest study to date on this issue, Liu et al (2020) estimated rates of evolution of upper and lower niche limits for 2087 species of plants and vertebrates and detected substantial differences between these limits.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from these studies seems to suggest that lower-and upper-climatic niche limits might be uncoupled over evolutionary time, such that patterns of climatic niche breadth might be driven more by changes in one of the climatic niche boundaries, particularly in the case of temperature. However, despite this indirect evidence, few studies have directly assessed variation in evolutionary rates between different climatic range limits (Carscadden et al, 2020). In the largest study to date on this issue, Liu et al (2020) estimated rates of evolution of upper and lower niche limits for 2087 species of plants and vertebrates and detected substantial differences between these limits.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has focused on drivers shaping the spatial distribution of dietary and habitat specialization at a large spatial scale (Belmaker et al, 2012;Mimet et al, 2019;Rivas-Salvador et al, 2019). However, a deeper understanding of additional life-history characteristics constricting the survival of specialist species is essential (Carscadden et al, 2020) S8). Akaike's information criterion values for each model performed in this study are shown in the Supporting Information (Table S9).…”
Section: Spatial Distribution Of Avian Specializationmentioning
confidence: 99%
“…Niche theory is as old as ecology 1 and the concept of the fundamental niche 2 holds prominence, well beyond the environmental sciences, in areas as diverse as evolutionary theory 3 and cell biology 4 . The fundamental niche describes all environmental circumstances that allow a species to grow in numbers 2,5,6 and is assumed fixed, for as long as the genotypic composition of the species stays the same 7 .…”
Section: Main Textmentioning
confidence: 99%